Uji Model Detail Desain Tanggul Laut Semarangx - Suprapto Suprapto; Juventus Welly Ginting (JURNAL TEKNIK HIDRAULIK, 2018)
The implementation of a detailed test model for the design of the Semarang sea wall was carried out to determine the level of stability of the sea dike structure in the form of cube-shaped concrete block armor with 1 m side. Besides, a test model was also conducted to evaluate the elevation of the sea dike against various wave conditions and increase in water level due to land subsidence. The Semarang sea wall was designed to with stand waves and tides, as well as toll roads, so that the model test was carried out to test the stability of the protective and runoff layers. There are 5 test scenarios carried out, namely LS01, LS05, LS10, LS15 and LS15-120% where each scenario shows land subsidence that occurs after 1 year, 5 years, 10 years and 15 years assuming the amount of land subsidence in Semarang 0 , 1 m / year. The test model results show that the stability of the protective armor structure with the concrete cube is quite high, as evidenced by the damage level which is quite low (NoD <0.5) in all conditions of the test scenario. Runoff starts in the LS 10, LS 15 and LS 15 scenarios 120% for 1,192 lt / dt / m, 6,588 lt / dt / m and 20,215 lt / dt / m, respectively. The runoff that occurs can be categorized functionally unsafe for vehicles in status (unsafe at any speed) while for the condition of the structure it is categorized as no damage. Therefore, a comprehensive evaluation of the stability and elevation / peak elevation needs of the embankment needs to be carried out after a 10-year service period.